Lesões bucomaxilofaciais: estudo dos casos periciados de 2007 a 2013 no Instituto Médico Legal Nina Rodrigues - Salvador / BA - Dias, Isabella de Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The maxillofacial trauma is one of the issues most important public health in the world, influenced by factors of social, cultural and economic. The functional and anatomical changes caused by physical damage can affect the individual psychologically, by the loss or impairment of chewing ability, speech and aesthetics. The peculiarities of the lesions, this study aimed to describe the epidemiological profile, assessing victims as well as the types, causes and resulting from maxillofacial trauma caused by violence and accidents, and injuries caused by dental work. The methodological design of the study was analytical-descriptive, cross-sectional, and were evaluated retrospectively from January 2007 to December 2013, 3,600 periciados of reports with head and neck injuries treated in the Dental Clinic of the Institute of Forensic Medicine Nina Rodrigues, Salvador BA. We evaluated 3,455 reports relating to assaults, traffic accidents and accidents in general, relating to socio-demographic profile, affected region, damage, and resulting etiologic agent. The data in this block were analyzed by chi-square test or the chi-square test of the likelihood ratio, defined using the V Cramer coefficient to quantify the association. It was found that there was a higher prevalence of cases involving 56.06% male, 80.72% and 72.19% adults faiodermas; of abuse has significant number of occurrences (74.18%), reaching the hard and soft tissues (42.72%). It was identified as well, the predominance of dento-alveolar lesions compared to the total number of maxillofacial trauma (67.73%); caused by blunt agent (92.72%)...

O traumatismo bucomaxilofacial representa um dos problemas de saúde pública mais importante do mundo, influenciado por fatores de ordem social, cultural e econômico. As alterações funcionais e anatômicas provocadas pelo dano físico podem afetar o indivíduo psicologicamente, pela perda ou diminuição de capacidade de mastigação, fonação e estética. Pelas particularidades das lesões, este trabalho objetivou delinear o perfil epidemiológico, avaliando as vítimas, bem como os tipos, causas e resultantes dos traumas bucomaxilofaciais por violências e acidentes, e as injúrias causadas por intervenção odontológica. O desenho metodológico do estudo foi analítico-descritivo, de corte transversal, e foram avaliados, retrospectivamente do período de janeiro de 2007 a dezembro de 2013, 3.600 laudos de periciados que apresentavam lesões de cabeça e pescoço, atendidos na Clínica Odontológica do Instituto Médico Legal Nina Rodrigues, Salvador- BA. Avaliaram-se 3.455 laudos referentes a agressões, acidentes de trânsito e acidentes em geral, relacionando com perfil sociodemográfico, região acometida, dano, agente etiológico e resultante. Os dados neste bloco foram analisados pelo teste de qui-quadrado ou por meio do teste de qui-quadrado da razão de verossimilhança, sendo definido o uso do coeficiente de V de Cramer para quantificação da associação. Constatou-se que houve maior prevalência de casos que envolviam 56,06% homens, 80,72% pessoas adultas e 72,19% faiodermas; as agressões apresentaram relevante número de ocorrências (74,18%), atingindo os tecidos duros e moles (42,72%). Identificou-se, também, a predominância de lesões dento-alveolares em relação ao número total de traumas bucomaxilofaciais (67,73%); causados por agente contundente (92,72%)...
Keywords: Traumatismos maxilo-faciais; Epidemiologia; Odontologia legal; Epidemiology